Principles of glacier mechanics - Hooke, Roger LeB (Cambridge University Press, 2005)
This book, first published in 2005, provides students and practising glaciologists with the tools they need to understand modern glaciology. Relatively simple concepts are introduced first, followed by mathematically more sophisticated chapters. A knowledge of basic calculus is assumed, but important concepts of physical processes are developed from elementary principles. Emphasis is placed on connections between modern research in glaciology and the origin of features of glacial landscapes. Student exercises are included. This new edition builds on the successful first edition: it has been completely updated, and important new sections and whole chapters have been added. Principles of Glacier Mechanics is designed to be used as a primary textbook in upper division and graduate courses in glaciology, and can be used as either a primary or supplementary text in courses in glacial geology. Practising glacial geologists and glaciologists will also find it useful as a reference book.